Guacamole powder: an innovative development from the investigation - ESTRADA M., Eliana; CORTÉS R., Misael; GIL, Jesús (Vitae, 2017)
Rationale: Guacamole is a sauce or dressing composed of avocado pulp and other ingredients. Guacamole powder is an important advancement in the generation of added value for the avocado production chain, as it is an alternative product with the potential to be used by end consumers. Aims: The aim of this study was to standardize the spray drying process for guacamole powder using the response surface methodology. Methods: Four independent variables were taken into account for the experiment design: atomizing disk speed (ADS), air inlet temperature (AIT), air outlet temperature (AOT) and vacuum pressure (VP). In addition, the following dependent variables were considered: water activity (aw), moisture (Xw), solubility (S), hygroscopicity (H), color (L*, a* and b*), extractable oil content (EO), peroxide index (PI) and particle size (D10, D50 and D90). Likewise, the following two dependent variables associated with the process were identified: yield (Y) and deposit formation (DF). Results: The best conditions for the process were obtained with ADS = 27451 rpm, AIT = 168ºC, AOT = 90ºC and VP = 1.77 ″H2O. These conditions yielded guacamole powder with the desired properties, namely: maximum Y, S, L*, b*, EO and minimal DF, aw, Xw, H, a*, PI, D10, D50, D90. Conclusions: The spray drying process is an effective technology that provides added value to avocado, the ADS being the independent variable that has the greatest impact on the quality of powdered guacamole.